Hello red fox - Carle, Eric (Aladdin Paperbacks, 2001)
Mama Frog gets a big surprise when the guests arrive for Little Frog's birthday party: Red Fox looks green to her! Orange Cat looks blue! What has gone wrong? With the active help of the reader, Little Frog shows Mama Frog how to see the animals in their more familiar colors. Is it magic? No, it's a remarkable function of the human eye. As Little Frog demonstrates, anyone can do it. Small readers will enjoy taking part in the fun of changing the colors of the animals. And they will laugh at the effect they themselves can create at the end of the story when Mama Frog gives Little Frog an embarrassing birthday kiss! Eric Carle believes that learning should be a joyful experience. In this imaginative book he invites young readers to discover complementary colors while enjoying the amusing story of Little Frog and his colorful friends.